PERAN RADIO REPUBLIK INDONESIA SEBAGAI PENYAMBUNG ASPIRASI MASYARAKAT DI DAERAH PERBATASAN PROVINSI KEPULAUAN RIAU - Putri, Nur A. Dwi (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2017)
Public Radio Broadcasting the Republic of Indonesia is one of the media that plays an important role in conveying information, connecting people's aspirations, as well as information safety belts, especially in border areas such as Riau Islands Province in other media. This is due to the lack of infrastructure in the border area and still not sovereign airspace of the republic of Indonesia especially for the region around the Riau Archipelago province. Therefore, the government is expected to pay more attention to RRI in the border areas. Because considering that RRI in the boundary area is not a regular radio but foreign radios that have sophisticated technology and have a broad transmit power and of course the central government should continue to try to take over the territorial sovereignty of Indonesian republic so that RRI can freely to run its role as seat belt information.